Another Step Towards Indexation of the SPDV Journal in 2018 - Margarida Gonçalo (Sociedade Portuguesa de Dermatologia e Venereologia, 2018)
Mais um Passo para a Indexação da Revista da SPDV em 2018 After 2 full years of publication with the new editorial board, 2017 was the year of big changes for the SPDV journal, which we hope will allow the indexation of our journal in the Medline. We had regular and timely publications, each number with an editorial related to one of the main articles published in that number, a continuous medical education (CME) article, followed by 6 articles with original data or review articles on the latest news on dermatology, 6-7 clinical cases, a quiz/what's your diagnosis presentation taking profit of clinical and histological images and letters to the editors. This format will continue in 2018 to have a more regular type of articles in our journal. 2017 was the year of internationalization. Apart from regular Brazilian clinical cases that we really appreciate as most bring new aspects from diseases that are seldom seen among us, we had a CME article on pruritus written by our colleague Manuel Pereira from Germany that with Sonja Ständer and the Munster team is coordinating European studies on pruritus and chronic prurigo, and an editorial written in collaboration with An Goossens the well-known teacher in contact and photocontact allergy from Leuven, Belgium. We are still expecting that our residents or specialists who stay a few months abroad in highly specialized centres with scholarships from the SPDV write review articles in collaboration with the doctors they worked with abroad. This year we began the process of identifying the papers published in our Journal with a DOI (digital object identifier), a direct link to the manuscript that includes the number given to our Journal followed by its initials, the volume and number of each journal and the consecutive number attributed by the webpage to each article that is submitted (ex. https://dx.doi.org/10.29021/spdv.76.2.849). Therefore online submission of all the manuscripts is mandatory. But this is an easy process and allows the authors to trace the state of their manuscripts while in review. It is also our intention in 2018 to begin the process of showing the articles online as soon as they are accepted, before their inclusion on the printed and finally composed volume. We hope to have the collaboration of Dr. José Carvalho who is thoroughly taking care of our webpage.   Thanks to the work of the editorial board and the many invited reviewers* and with a more thorough reviewing process we improved the quality of the papers that we received, although many of them were already of really high standard. Happily this year more original and review articles were submitted (33) of which only 2 were rejected (6%). The rejection rate was much higher within the 75 clinical reports received (38% - 51%). Although some articles submitted in 2017 are still under review the overall rejection rate was around 36%. With the final review of Drª Helena Donato there is a good standardization of procedures, including a critical review of the references, MeSH words and inclusion of all the missing details in the manuscripts to fulfil the international standards for publication of scientific papers. The work of our Editor, Gabriela Marques Pinto, who also makes a final review of all the manuscripts and prepares their composition for printing is also an enormous job. It is our intention to renew the editorial board during 2018 to include other colleagues that have given a significant and timely contribution to our journal, but we will keep the contribution of Dr Helena Donato and her knowledge to submit the journal for indexation with the next number of 2018. Still, to keep with international rules of scientific journals, in 2018 we will change the placing of publicity within the printed journal to avoid its inclusion in the middle of scientific papers. With these changes and improvements we are feeling more confident and on a much better position to achieve indexation of the Revista da SPDV at the Medline. With the contribution of this team and all the dermatologists we hope a favourable decision, but this will be just one step forward as we will certainly keep on improving the Journal of Portuguese-speaking dermatologists.